Sustainable Management of Climate Change: The Case of the Middle East and North Africa Region - Adel M. Al Taweel; V. Ismet Ugursal; Donnie Boodlal (Renewable Energy and Sustainable Development)
Climate change is one of the major environmental challenges facing the world. Particularly vulnerable are arid and low-laying coastal areas, conditions that prevail through most of the Middle East and North Africa [MENA]. This region is an economically diverse one, including both the oil-rich economies in the Gulf and countries that are resource-scarce in relation to their population.  However, with about 23 percent of MENA’s population living on less than $2 a day, it is imperative that the climate change management strategies adopted be cost-effective and emphasize economic, social and human development while addressing the concerns arising from anthropogenic climate change. Over the past decades several national and international mechanisms were developed in an attempt to reduce the emissions considered to be mainly responsible for climate change, and to assist in coping with the adverse effects that are beginning to occur as a result of climate change. Unfortunately, many of these approaches are presently associated with economic penalties that often adversely affect the socio-economic welfare of the populace, particularly in low-, and medium-income countries. In this regard, it is informative to note the experience recently gained by Trinidad and Tobago [T&T] in its attempt to reduce GHG emissions without affecting the competitiveness of the industrial and agricultural sectors. Using appropriate decision making tools and a policy environment based on a combination of regulations and incentives, the environmental challenges can be turned into a vehicle for sustainable development. This paper discusses the factors that need to be considered while developing a sustainable climate change management approach for the MENA region and develops some recommendations that may be essential for achieving the desired climate change mitigation/adaptation actions while minimizing social disruption.